Effect of bulk temperature on formation of crude oil fouling precursors on heat transfer surfaces - Shetty, N. (Trans Tech Publications Ltd, 2014)
Temperature plays a very important role in the formation of fouling precursors in crude oils which is considered to be the first step before the precursors are either attached to the wall as a deposit or transferred back to the bulk fluid by diffusion. In order to investigate the formation characteristics of fouling precursors in crude oils at different bulk temperatures, a custom-design thin film microreactor is constructed. It is observed during the experiments that tendency to form fouling precursors is higher at higher surface temperatures. The precursor particles once formed continue to grow in size with time at constant surface temperatures. It is also observed that the particles tend to grow in size while it is cooled when the temperatures are below 55 Í¦C. Â© 2014 Trans Tech Publications, Switzerland.